2016
DOI: 10.1111/jog.13172
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis reveals candidate mRNA and their potential roles in uterine leiomyomas

Abstract: In conclusion, our study observed that a set of aberrantly expressed genes and the related biochemical pathways may lead to transformation of normal myometrium in pathological focuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…There have been controversies about the effect of ALDH1A1 on uterine leiomyoma. Zaitseva and coworkers found that αSMAnegative fibroblast-like cells of the connective tissue strongly expressed ALDH1A1 in myometrium when compared with uterine leiomyoma [25], which was consist with the research of Xia and colleagues [26]. ALDH1A1 expression was regulated differently in myometrial and fibroid cells by retinol metabolism pathway which may be important in fibroid pathophysiology [27].…”
Section: Fig 10 Transcriptional Expression Of Hub Genes In 20 Different Types Of Cancer Diseases (Oncomine Database)mentioning
confidence: 53%
“…There have been controversies about the effect of ALDH1A1 on uterine leiomyoma. Zaitseva and coworkers found that αSMAnegative fibroblast-like cells of the connective tissue strongly expressed ALDH1A1 in myometrium when compared with uterine leiomyoma [25], which was consist with the research of Xia and colleagues [26]. ALDH1A1 expression was regulated differently in myometrial and fibroid cells by retinol metabolism pathway which may be important in fibroid pathophysiology [27].…”
Section: Fig 10 Transcriptional Expression Of Hub Genes In 20 Different Types Of Cancer Diseases (Oncomine Database)mentioning
confidence: 53%
“…Hsa_circ_0056686 is an exon circRNA formed by splicing of the KIF5C mRNA precursor. KIF5C was reported to be involved in the progression of ULM and closely related to ERS [ 15 , 16 ]. The present study showed that hsa_circ_0056686 was upregulated in ULM tissues, which was consistent with those reported by Wang et al suggesting that hsa_circ_0056686 was highly expressed in ULM and was positively related with the leiomyoma size [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent findings using calpain-6 regulatory sequence–based reporter assays identified calpain-6 as a target gene for a stemness pathway in embryonic stem and cancer cells 33 . Researchers found that calpain-6-expressing cells were tumor-initiating and conferred the property of chemoresistance 37–41 , suggesting an association between calpain-6 and the malignant characteristics of sarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Calpain-6 was found to be aberrantly expressed in different tumors, and it exhibits both anti-apoptotic and pro-angiogenic functions. Calpain-6 is overexpressed in many types of tumors and induces apoptosis resistance, cell proliferation, and angiogenesis in tumors 37–41 . The association between elevated calpain-6 expression and the inhibition of apoptosis and chemoresistance 37,39,43 suggests its role in the malignant progression of primary tumors.…”
Section: Discussionmentioning
confidence: 99%